Constraining the Source Regions of Pulsating Auroras. Issue 17 (6th September 2019) - Grono, Eric; Donovan, Eric
Abstract: Pulsating auroras have often been erroneously discussed as if they are a single phenomenon. For this reason, the relationship between different pulsating auroras is poorly understood. Grono and Donovan (2018, https://doi.org/10.5194/angeo-36-891-2018 ) subcategorized pulsating auroras into amorphous pulsating, patchy pulsating, and patchy auroras, which are separable based on their pulsation and structuring. By comparing the latitudes of these auroras to the location of the proton aurora, we have constrained their source regions for the first time. Pulsating aurora does not occur poleward of the proton aurora. Amorphous pulsating aurora occurs within and equatorward of the proton aurora, while patchy pulsating and patchy auroras predominantly occur equatorward of the optical b2i boundary. This indicates that the characteristic structuring of the patchy auroras is unable to form outside of the mostly dipolar inner magnetosphere, but the wave‐particle interactions that produce auroral pulsations are less constrained, extending into the transition region where the magnetic field begins to stretch. Plain Language Summary: The aurora is the projection of dynamic plasma processes onto the upper atmosphere. By viewing the aurora, we can remote sense these dynamics on a large scale that is otherwise impossible, but only if we understand how they are created. Pulsating auroras are perhaps the most common early morning aurora, peaking in activity between midnight and sunrise, and yet they have traditionally been researched by our scientific community as if they are a single phenomenon. Recent work has begun to differentiate pulsating auroras and identify their specific causes. This study discovers the limits of these auroras' source regions. Key Points: The source regions of pulsating auroras are constrained relative to the proton aurora Pulsating aurora does not occur poleward of the proton aurora Patchy and patchy pulsating auroras originate from where the magnetosphere is mostly dipolar